Capture and commercialization of blue land crabs ("guaiamum") Cardisoma guanhumi (Lattreille, 1825) along the coast of Bahia State, Brazil: an ethnoecological approach - Firmo Angélica MS; Tognella Mônica MP; Silva Saulo R; Barboza Raynner RRD; Alves Rômulo RN (BMC, 2012)
Abstract Background Blue Land Crab (Cardisoma guanhumi) is one of the most important crustacean species captured and commercialized in Brazil. Although this species is not considered to be threatened with extinction, populations of C. guanhumi are known to be rapidly diminishing due to heavy harvesting pressures and degradation of their natural habitats, highlighting the necessity of developing and implanting management and protection strategies for their populations. There have been no ethnozoological publications that have focused specifically on C. guanhumi, in spite of importance of this type of information for developing efficient management plans of resource utilization. So, the present work describes the ethnoecological aspects of the capture and commercialization of C. guanhumi by a fishing community in northeastern Brazil. Methods Field work was carried out in the municipality of Mucuri, Bahia in Brazil, between the months of January and March/2011 through the use of open semi-structured interviews with all of the crustacean harvesters in city who acknowledged their work in capturing this species, totaling 12 interviewees. The informants were identified through the use of the "snowball" sampling technique. In addition to the interviews themselves, the "guided tour" technique and direct observations was employed. Results According all the interviewees, the C. guanhumi is popularly called "guaiamum" and is collected in "apicum" zones. They recognize sexual dimorphism in the species based on three morphological characteristics and the harvesters also pointed two stages in the reproductive cycle during the year and another phase mentioned by the interviewees was ecdysis. All of the interviewed affirmed that the size and the quantities C. guanhumi stocks in Mucuri have been diminishing. All of the interviewees agreed that the species and other mangrove resources constituted their principal source of income. The harvesters dedicated three to five days a week to collect Blue Land Crabs and the principal technique utilized for capturing is a trap called a "ratoeira" (rat-trap). Conclusions The results of the present work demonstrated that the community retains a vast and important volume of knowledge about C. guanhumi that could subsidize both scientific studies and the elaboration of viable management and conservation strategies for this species.